Integration in Asia and Europe Historical Dynamics, Political Issues, and Economic Perspectives - Welfens, Paul J.J; Knipping, Franz; Chirathivat, Suthiphand (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Broadening and deepening of economic and political integration are hallmarks of the EU and ASEAN. This book critically analyses the economic and institutional changes in both Europe and Asia. There is considerable potential for instability, but one also finds regional growth opportunities. Comparative policy analysis and evaluation of various cooperation strategies are presented. Emphasis is on banking, financial market dynamics, ICT, and macroeconomic policies as well as trade, energy, and environmental issues. Legal aspects are combined with historical and economic perspectives. Due emphasis also is on the impact of China and the role of international organisations. The comparative analysis of EU and ASEAN integration suggests important policy choices, including those at the multilateral level.